Predictors of obstructive sleep apnea in snorers - Ibrahim Abdulsalam; Almohammed Ahmed; Allangawi Mona; A Sattar Hisaham; Mobayed Hassan; Pannerselvam Balamurugan; Philipose Mary (Annals of Saudi Medicine, 2007)
Background: Snoring is a common problem that poses a high risk for obstructive sleep apnea (OSA). We studied the contribution of risk factors for OSA in snorers referred for full-night polysomnography (PSG). Methods: A questionnaire was administered to subjects referred for PSG in the period from April 2002 to March 2005. Results: There were 191 (84%) snorers identified by 227 PSG studies. They had a mean age of 48.1±9.8 years, (age range, 23-73 years) and 78.5% were males. OSA as indicated by a respiratory disturbance index (RDI) of> 5 events/hour was seen in 126 (66%) subjects. In males, 72.7% had OSA, with a mean RDI of 43.0±26 events/hour, versus 39% with OSA in females with a mean RDI of 27.8±26.5 events/hour (P< 0.001). The OSA group had a higher mean Epworth Sleepiness Scale (ESS) (P< 0.001), a larger mean neck circumference (P< 0.01), an increased mean age (P< 0.05), and more witnessed apneas (P< 0.001) but not choking (P=0.096). The mean increase in body mass index was linked to OSA only in females (P< 0.05) but not in the overall study (P=0.507). Multivariate analysis showed that ESS, male gender, and a history of witnessed apnea were associated with OSA, while controlling for obesity, large neck circumference, age, and history of choking. Conclusion: In screening snorers for PSG, male gender, ESS and a history of witnessed apneas were the most important predictors of OSA, but other factors should be considered in referring snorers for PSG. In males, obesity did not contribute to the risk of OSA in our study population.